Improving the ozone gas-sensing properties of CuWO4 nanoparticles - Catto, Ariadne C. [UNESP]; Fiorido, Tomas; Souza, Erica L. S.; Avansi, Waldir; Andres, Juan; Aguir, Khalifa; Longo, Elson [UNESP]; Cavalcante, Laecio S.; Silva, Luis F. da (Elsevier B.V., 2018)
This paper consists of an experimental investigation on the effects of annealing temperature on the structural, surface and ozone gas-sensing properties of CuWO4 nanoparticles prepared via a sono-chemical route. X-ray diffraction patterns and X-ray absorption near-edge structure spectroscopy revealed that both long-and short-order structures increase with the annealing temperature. Electrical resistance measurements indicated that CuWO4 samples were sensitive in the range of 15-1400 ppb, exhibiting a good reversibility and repeatability. The enhancement of the ozone gas-sensing properties was attributed to the reduction of hydroxyl species and the improvement of the crystallization degree. This study provides a versatile strategy for obtaining CuWO4 nanoparticles for practical applications as an ozone gas sensor. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Sonochemical; CuWO4; Surface; Chemiresistor; Ozone